Variable in size venous malformations. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
That a vascular lesion becomes more evident in all the situations that involve an increased intravascular pressure is well known and useful in the absence of other criteria to suspect such a diagnosis. The peculiarity of the two cases is that the lesion, little (case 2) or not at all (case 1) visible under normal conditions became visible in a coarse and transitory way with the crying or with variations of position of the head. Venous malformations are present from the earliest periods of life and tend to worsen very slowly over the years. It is known that intraorbital venous malformations can be associated with enophthalmos at standing patients and with exophthalmos at supine patients. Characteristic of venous malformations is the absence of thrills and the presence of phleboliths at palpation, and the slow flow on color doppler.